2022
DOI: 10.2215/cjn.14181021
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Diagnostic Criteria and Epidemiology of Acute Kidney Injury and Acute Kidney Disease in the Critically Ill Patient

Abstract: Since the description ischuria renalis by William Heberden (1), AKI has remained a prominent complication of critical illness. Beyond KRT, treatment has been limited by the capacity to phenotype this condition. Here, we chronicle the evolution of attempts to classify AKI, including the adoption of consensus definitions, the expansion of diagnosis and prognosis with novel biomarkers, and emerging tools such as artificial intelligence (AI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 124 publications
0
15
0
1
Order By: Relevance
“…14,18,19,21,54,55 Incomplete recovery after AKI results in renal fibrosis, the pathological accumulation of extracellular matrix (ECM) proteins, mainly collagens in the kidney. 56,57 We then explored the protein levels of α-smooth muscle actin (α-SMA) and collagen I (Col I) by Western blotting and immunofluorescence staining (Figure 4D,E,F,G). The expression levels of α-SMA and Col I were greatly increased after I/R injury but were significantly We selected 6−8 weeks male C57 mice, separated both kidneys, and clamped the bilateral kidney pedicle for 30 min to induce ischemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,18,19,21,54,55 Incomplete recovery after AKI results in renal fibrosis, the pathological accumulation of extracellular matrix (ECM) proteins, mainly collagens in the kidney. 56,57 We then explored the protein levels of α-smooth muscle actin (α-SMA) and collagen I (Col I) by Western blotting and immunofluorescence staining (Figure 4D,E,F,G). The expression levels of α-SMA and Col I were greatly increased after I/R injury but were significantly We selected 6−8 weeks male C57 mice, separated both kidneys, and clamped the bilateral kidney pedicle for 30 min to induce ischemia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that mitochondrial dysfunction and ATP reduction are intently relevant to CKD development and progression. ,,,,, Incomplete recovery after AKI results in renal fibrosis, the pathological accumulation of extracellular matrix (ECM) proteins, mainly collagens in the kidney. , We then explored the protein levels of α-smooth muscle actin (α-SMA) and collagen I (Col I) by Western blotting and immunofluorescence staining (Figure D,E,F,G). The expression levels of α-SMA and Col I were greatly increased after I/R injury but were significantly decreased after I/R injured cells were incubated with tFNAs, Typ, and TTC.…”
Section: Resultsmentioning
confidence: 99%
“…These barriers speak to the intrinsic challenges of this type of pragmatic EHR-based research and underscore the need to develop valid heuristics to identify diagnoses, syndromes, and interventions automatically from extant data in the EHR ( 20 , 33 ). Similarly, the inability to estimate baseline creatinine from many patients’ structured EHR data hampers efforts to scale dynamic renal failure models ( 34 , 35 ); in this example, we intentionally performed relevant sensitivity analyses to check the reliability of our baseline assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common condition in critically ill children affecting 24%–41% of children admitted to the paediatric intensive care unit (PICU) 1–4. It is now recognised as an independent predictor of PICU mortality1 2 5 and can lead to hypertension and chronic kidney disease (CKD) among survivors 6 7. In fact, AKI and CKD are now viewed as a continuum instead of two separate entities 7…”
Section: Introductionmentioning
confidence: 99%